ANALISIS PENGARUH PROFITABILITAS, LIKUIDITAS, DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN KUALITAS LABA SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI PERIODE 2020-2023 - Mohammad Fais Fadilatul Rifki; Ida Subaida; Febri Ariyantiningsih (Fakultas Ekonomi dan Bisnis, 2025)
Banking institutions play a central role in supporting economic stability and growth, particularly by acting as intermediaries between surplus fund holders and those in need of funds. Firm value in the banking sector serves as a key indicator for investors to assess the company’s prospects and financial health. This study aims to analyze the effect of profitability, liquidity, and capital structure on firm value, with earnings quality as an intervening variable, in banking companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. The research employs a quantitative method with a descriptive approach. The sampling technique used is purposive sampling, with a population of 47 banking companies, of which 10 companies met the specified criteria. Data were analyzed using Path Analysis with the Structural Equation Modeling (SEM) approach based on Partial Least Squares (PLS). The results of direct influence hypothesis testing show that profitability and capital structure have a statistically significant positive influence on earnings quality. However, liquidity has an insignificant negative effect on earnings quality. On the other hand, profitability and capital structure do not have a significant influence on company value. In fact, earnings quality has a significant negative influence on company value. Furthermore, earnings quality shows a negative but significant influence on company value. In addition, in testing the indirect influence hypothesis, it shows that Profitability, Liquidity and Capital Structure do not significantly influence company value through earnings quality as an intervening variable.